Climate legacy in seed and seedling traits of European beech populations - Pawłowski, Tomasz A.; Suszka, Jan; Mucha, Joanna; Zadworny, Marcin; Alipour, Shirin; Kurpisz, Barbara; Chmielarz, Paweł; Jagodziński, Andrzej M.; Chmura, Daniel J. (Frontiers in Plant Science, 2024)
Tree species' ability to persist within their current distribution ranges is determined by seed germination and seedling growth. Exploring variation in these traits in relation to climatic conditions helps to understand and predict tree population dynamics, and to support species management and conservation under future climate. We analyzed seeds and seedlings of 26 European beech populations from the northeastern boundary of the species range to test whether: 1) adaptation to climatic conditions is reflected in depth of dormancy and germination of seeds; 2) climatic characteristics of origin predictably affect seedling traits. The variation in seed dormancy and germination in a laboratory test, and seedling growth and morphology traits in a nursery commongarden test was examined. Populations originating from warmer and drier sites (mostly from the northern region), compared to those from the opposite end of climatic gradient, germinated later, with a lower success, and produced seedlings with shorter and tougher roots. They had deeper dormancy and poorer seed germination capacity, and are likely more vulnerable to environmental changes. The climatic conditions at the origin shape the intraspecific variation of seed germination and seedling traits, and may limit regeneration from seed and affect adaptation potential of beech to increasing temperatures and decreasing precipitation.